The Comparison of Fixed and Flexible Progestin Primed Ovarian Stimulation on Mature Oocyte Yield in Women at Risk of Premature Ovarian Insufficiency - Kalafat, Erkan; Dizdar, Merve; Turkgeldi, Engin; Yildiz, Sule; Keles, Ipek; Ata, Baris (Frontiers in Endocrinology, 2022)
While gonadotrophin releasing hormone (GnRH) antagonists have been the standard of pituitary suppression during ovarian stimulation for ART, progestin primed ovarian stimulation (PPOS) has emerged as an alternative. Progestins can be started simultaneously with gonadotrophins (fixed PPOS) or later in the cycle depending on follicle growth (flexible PPOS). However, the flexible and fixed PPOS regimens have not been directly compared as of yet. This was a retrospective cohort study including women with diminished ovarian reserve who underwent oocyte cryopreservation. All women underwent ovarian stimulation with a fixed 300 IU daily dose of FSH. The primary outcome was the number of MII oocyte retrieved per cycle. Secondary outcome measures included the incidence of premature LH surge (>10ng/mL) and number of follicles larger than 14mm on the day of maturation trigger. During the screening period 2 out of 97 cycles were cancelled before oocyte retrieval, one in each group yielding an overall cancelation rate of 2%. Among women who had oocyte retrieval, 65 underwent flexible and 30 fixed PPOS. At baseline women on fixed and flexible PPOS had similar age (mean difference: -2.17 years, 95% CI: -4.46 to 0.11) and serum AMH levels (mean difference: 0.10 ng/mL, 95% CI: -0.24 to 0.47). Slight imbalances between the groups were rectified with propensity score matching using age and AMH levels. The incidence of premature LH surge (RR: 1.47, 95% CI: 0.51 – 5.27, p = 0.50), follicle count larger than 14mm on hCG day (RR: 1.14, 95% CI: 0.93 – 1.42, p = 0.22), number of MII oocytes retrieved (RR: 0.95, 95% CI: 0.79 – 1.15, p = 0.61) were similar between flexible and fixed PPOS. The rate of no oocyte retrieval was same between the groups (0.0% both) but no formal estimation was possible. Flexible and fixed PPOS regimens had no appreciable differences regarding MII oocyte yield and the incidence of premature LH surges. Cycles without oocyte retrieval were rare in both groups and ultrasonographic parameters of gonadotropin response were similar. Our study suggests the performances of either progestin regimen are comparable in this group of women.